Is the Court of Justice Afraid of International Jurisdictions? (Polish Yearbook of International Law, 2017)
This article analyses the relationship between the Court of Justice and other international jurisdictions. In particular, it addresses the following question: To what extent is the Court of Justice ready to accept that some aspects of EU law are subject to the jurisdiction of an international body? The answer to this question requires analysis of the precise scope of the principle of autonomy of EU law as this principle could potentially constitute grounds on the basis of which the Court of Justice excludes the transfer of judicial competences to external bodies. For this reason, the article refers to the most important decisions in the feld: Opinions 1/91 and 1/92, Opinion 1/09, Opinion 2/13, judgment in C146/13 Spain v. Parliament and Council and judgment in C284/14 Achmea. It also discusses the consequences of the application of Article 344 TFEU.